Exogenous Gene Expression and Insect Resistance in Dual Bt Toxin Populus × euramericana ‘Neva’ Transgenic Plants - Ren, Yachao; Zhou, Xinglu; Dong, Yan; Zhang, Jun; Wang, Jinmao; Yang, Minsheng (Frontiers in Plant Science, 2021)
Bacillus thuringiensis (Bt) insecticidal protein genes are important tools in efforts to develop insect resistance in poplar. In this study, the Cry1Ac and Cry3A Bt toxin genes were simultaneously transformed into the poplar variety Populus × euramericana ‘Neva’ by Agrobacterium-mediated transformation to explore the exogenous gene expression and insect resistance, and to examine the effects of Bt toxin on the growth and development of Anoplophora glabripennis larvae after feeding on the transgenic plant. Integration and expression of the transgenes were determined by molecular analyses and the insect resistance of transgenic lines was evaluated in feeding experiments. Sixteen transgenic dual Bt toxin genes Populus × euramericana ‘Neva’ lines were obtained. The dual Bt toxin genes were expressed at both the transcriptional and translational levels; however, Cry3A protein levels were much higher than those of Cry1Ac. Some of the transgenic lines exhibited high resistance to the first instar larvae of Hyphantria cunea and Micromelalopha troglodyta, and the first and second instar larvae and adults of Plagiodera versicolora. Six transgenic lines inhibited the growth and development of A. glabripennis larvae. The differences in the transcriptomes of A. glabripennis larvae fed transgenic lines or non-transgenic control by RNA-seq analyses were determined to reveal the mechanism by which Bt toxin regulates the growth and development of longicorn beetle larvae. The expression of genes related to Bt prototoxin activation, digestive enzymes, binding receptors, and detoxification and protective enzymes showed significant changes in A. glabripennis larvae fed Bt toxin, indicating that the larvae responded by regulating the expression of genes related to their growth and development. This study lay a theoretical foundation for developing resistance to A. glabripennis in poplar, and provide a foundation for exploring the mechanism of Bt toxin action on Cerambycidae insects.